Managing Director's Global Policy Agenda to the International Monetary and Financial Committee : Confront Global Challenges Together. (Policy Papers; Policy Paper, 2015)
Against a backdrop of declining oil prices, sharp variations in exchange rates, and market volatility, global growth remains uneven. The prospect of a new mediocre lingers as medium-term forecasts have been marked down since the last GPA. Promoting balanced, sustained growth requires an integrated policy package that bolsters today's actual and tomorrow's potential output, diminishes risks, and confronts emerging global challenges. Watch the Video The Executive Summary is also available in: Arabic , Chinese, French, Japanese, Russian, and Spanish.